The value of village convention in educating traditions of culture, morality and lifestyle for Vietnamese people in the feudal period - Loi, Le Van (Linguistics and Culture Review, 2021)
Village convention is a code of conduct that is considered a model, which is voluntarily agreed, drafted, promulgated by the traditional Vietnamese rural communities, and takes effect within a residential area, usually a village or a commune, used as a measure of dignity, personality and adjustment of social relations in the life, production and labor of the communities. In the process of existence and development, the village convention has experienced many ups and downs in history and has been handed down by the Vietnamese communities for many generations. The article summarizes the process of formation, basic content and value of village convention in the education of traditions of culture, morality and lifestyle for Vietnamese people in the feudal period and makes recommendations for inherit and promote those values in Vietnamese society today.